Whose crisis? Russian Intelligentsia and the Ukrainian Question - Coming to Terms - Riabchuk, Mykola (Porównania, 2014)
The ongoing Russo-Ukrainian war euphemistically defined as the “Ukrainian crisis”, brought to the fore, once again, a striking inability of the Russian cultured and educated stratum to come to terms with Ukraine’s cultural distinctness and political sovereignty, and to withstand soberly the unscrupulous propaganda of the Kremlin regime. The paper examines reaction of Russian intelligentsia to what they perceive as the “Ukrainian crisis” and searches for historical and cultural roots of what is in fact a profound crisis of Russian identity and nationhood.